2007
DOI: 10.1038/sj.pcan.4501003
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressants and risk of prostate cancer: a nested case – control study

Abstract: Although the association between antidepressant drug use and risk of cancer has received considerable attention in the past years, no work has been done specifically on prostate cancer. We carried out a population-based case -control study to assess the risk of prostate cancer in association with exposure to tricyclic antidepressants (TCAs) and selective serotonin reuptake inhibitors (SSRIs). 7767 prostate cancer cases diagnosed between 1981 and 2000 were accrued through the Saskatchewan Cancer Agency. Saskatc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
2

Year Published

2008
2008
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 35 publications
1
17
0
2
Order By: Relevance
“…Some of the above studies have controlled for some of these additional factors. 31,[33][34][35]52,56 With or without these controls, the 7 lines each provide circumstantial evidence that is consistent with the elevated NE etiological hypothesis. They are also to some degree independent of one another, further strengthening the hypothesis.…”
Section: Literature Search Detailssupporting
confidence: 53%
See 2 more Smart Citations
“…Some of the above studies have controlled for some of these additional factors. 31,[33][34][35]52,56 With or without these controls, the 7 lines each provide circumstantial evidence that is consistent with the elevated NE etiological hypothesis. They are also to some degree independent of one another, further strengthening the hypothesis.…”
Section: Literature Search Detailssupporting
confidence: 53%
“…To provide the reader with a feel for the numbers, here are a few of the SIRs and odds ratios. In the prostate cancer study, 31 the rate ratios for tricyclics increasing prostate cancer risk were 1.31 (95% CI 1.14-1.51), 1.58 (95% CI 1.29-1.93) and 2.42 (95% CI 1.87-3.12) at the low, medium and high average daily dose levels, respectively. In the lung cancer study, 35 SSRI use during the year preceding the index date with treatment duration of at least 1 year had an odds ratio of 0.59 (95% CI 0.41-0.86).…”
Section: Literature Search Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have demonstrated that antidepressants decrease the risk of breast cancer development (1)(2)(3)(4). On the other hand, several studies have reported that antidepressants increase the risk of nonHodgkin lymphoma and prostate cancer (5,6), and it is still controversial what effect tricyclic antidepressants have on lung, breast and colon cancer cells (7)(8)(9). Both in vitro and in vivo studies indicate antidepressants are cytotoxic to most malignant cells, particularly colon and breast cancer (10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…For DNA fragmentation analysis, the cells were plated on a 10-mm culture dish at a density of 2x10 6 cells/dish and exposed to different concentrations of DMI for 24 h. The cells which attached to the bottom of the dish were scraped off and collected together with unattached cells by centrifuging at 800 x g for 5 min at 4˚C. The DNA was prepared from the pelleted cells and applied to a 2% agarose gel containing 0.5 mg/ml of ethidium bromide for electrophoretic analysis.…”
Section: Dna Fragmentation Analysismentioning
confidence: 99%